Modern dynamic reliability analysis for multi-state systems : stochastic processes and the Lz-transform /: stochastic processes and the Lz-transform. (2020) - Lisnianski, Anatoly; Frenkel, Ilia, 1950-; Khvatskin, Lev
No abstract available